Quality Assurance and Support Measures for Solar Cooling on System Level. (June 2016) - Morgenstern, Alexander; Fedrizzi, Roberto; Selke, Tim; Beccali, Marco; Mugnier, Daniel; Pietruschka, Dirk; Neyer, Daniel
Abstract: Within the IEA SHC Task 48 "Quality assurance and support measures for Solar Cooling" the analysis and evaluation of the systems has been one of the four main focuses. Here the activities are including the lab- and field-based characterization of the systems, the definition and application of performance figures, a guideline for a reliable monitoring procedure including methods for automated error detection and an updated overview on worldwide installed DEC systems including hints and good practice examples. They are furthermore leading to three different easy-to-use tools for solar cooling systems: The LCA tool considers environmental and energetic values for the evaluation, the PISTACHE tool offers a fast pre-sizing of the systems giving support for the planner in advance and finally an Excel tool allows a complete system evaluation using long term monitoring data.